Effect of resin content on the properties of Oriented Strand Board from ludai / Mohd Hafiz Musa - Musa, Mohd Hafiz (2003)
Oriented strand board (OSB) production in Malaysia is still at its fancy. In United States and Canada, OSB was well accepted for construction purpose. Today, OSB panels are recognized for the same uses as plywood. But in Malaysia OSB is not quit popular. In this study, ludai (Sapium Baccatum) was used as raw material for the manufacture of OSB. Ludai are grown widely in large area in Malaysian's forest. Currently, the ludai species is underutilized. This is because rubberwood are still used as raw material in wood panel products. Somehow rubberwood will decrease. So ludai will be the substitute to the rubberwood. In this study, the effect varying resin content of ludai OSB on some strength and physical properties was studied. In general, the strength properties [modulus of rupture (MOR) and modulus of elasticity (MOE)] increased with increase in resin content. The physical properties [thickness swelling (TS) and water absorption (WA)] generally improved with increase in resin content.